1994
DOI: 10.1007/bf00043887
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a cDNA encoding a 70 kDa heat-shock cognate protein expressed in vegetative tissues ofArabidopsis thaliana

Abstract: A cDNA encoding a 70 kDa heat shock 'cognate' protein (hsc70) was isolated from Arabidopsis thaliana by using a rat hsc70 cDNA as probe. Sequence analysis demonstrated the conservation of functional domains and important amino acid residues among hsc70s in plants and animals. The expression of this gene was stress-inducible, and was found at a substantial level during normal growth in root, stem, leaf and flower tissues, but not in siliques. Multiple copies of this gene exist in the Arabidopsis genome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…5 and 6). The induction of Hsc70-1 and BiP expression in response to heat shock was in good agreement with previous findings by other laboratories using hybridization-based techniques (Wu et al, 1988(Wu et al, , 1994Koizumi, 1996).…”
Section: Diverse Responses Of Arabidopsis Hsp70s To Temperature Extremessupporting
confidence: 92%
See 3 more Smart Citations
“…5 and 6). The induction of Hsc70-1 and BiP expression in response to heat shock was in good agreement with previous findings by other laboratories using hybridization-based techniques (Wu et al, 1988(Wu et al, , 1994Koizumi, 1996).…”
Section: Diverse Responses Of Arabidopsis Hsp70s To Temperature Extremessupporting
confidence: 92%
“…Previous expression studies for plant hsp70s demonstrated induction in 2 h of heat shock either at 37°C or 40°C (Wu et al, 1988(Wu et al, , 1994DeRocher and Vierling, 1995;Koizumi, Wu et al, 1996;Li et al, 1999). Most Arabidopsis hsp70s reached peak induction within 30 min of heat shock exposure, and the rapid response of hsp70 genes to heat shock is not limited to Arabidopsis, as the induction of spinach hsp70 genes was detected as early as 5 min after heat shock (Q.…”
Section: Temperature Responsementioning
confidence: 97%
See 2 more Smart Citations
“…This may be due to the fact that heat and drought stress often coincide. However, ABA can induce thermo-tolerance in maize and it can activate some genes encoding heat shock proteins (Wu et al 1994;Gong et al 1998). In addition, heat-resistant dwarf mutants can be made sensitive to heat stress by GA treatment (Barnabás et al 2008).…”
Section: Heat Stressmentioning
confidence: 99%